2010
DOI: 10.1007/s11085-010-9198-2
|View full text |Cite
|
Sign up to set email alerts
|

On the Oxidation and Nitridation of Chromium at 1300 °C

Abstract: Chromium can be a candidate of interest as a base component for refractory alloys for high temperature applications. Few data are available about oxidation kinetic of chromium in air for temperature as high as 1300°C. Moreover, rare papers take the nitridation of chromium into account in the description of the oxidation process or in the calculation of the kinetic constants. In the present study, global methods like thermogravimetry were linked to thickness measurements and microstructural characterisation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…This finding is in agreement with literature. For instance at 1373 K (100 K higher than the temperature investigated in our study) a sublimation rate of 2.5 × 10 −7 mg cm −2 s −1 was found [44]. In contrast WO 3 sublimates significantly as shown in Figure 3a.…”
Section: Evaluation Of the Oxidation Performancementioning
confidence: 51%
“…This finding is in agreement with literature. For instance at 1373 K (100 K higher than the temperature investigated in our study) a sublimation rate of 2.5 × 10 −7 mg cm −2 s −1 was found [44]. In contrast WO 3 sublimates significantly as shown in Figure 3a.…”
Section: Evaluation Of the Oxidation Performancementioning
confidence: 51%
“…Tests interrupted after 16 and 24 h also showed similar disintegration of the mixed oxide layer along with severe mass gains. Studies of the oxidation of pure chromium at 1300 C have revealed that although evaporation of CrO 3 is observed, the rate of oxidation of Cr 2 O 3 to CrO 3 (g) is surpassed by the rate Cr oxidation [33]. With rapid loss of Cr from the matrix, the relative concentration of silicon increases in the alloy, particularly close to the specimen surface, and the inward diffusion of oxygen into the substrate results in the formation of silica particles embedded in the solid solution matrix.…”
Section: Oxidation Mechanism 1300 Cmentioning
confidence: 99%
“…Earlier works showed that two or three step reduction pathway of unsupported CrO3 is or may be accompanied by simultaneous decomposition of intermediate CrOx phases (Cr3O8 and Cr5O12), which are eventually transformed into crystalline Cr2O3 at about 500 °C [12,13] of magnitude higher than the parabolic oxidation constant. Other Experiments demonstrated that the presence of nitrogen in the substrate is always a precursor to breakdown of the oxide layer and does not result from diffusion through the Cr2O3 Layer [14] . The present research intended to investigate the thermal properties of chromium nitrate under different temperature conditions.…”
Section: Introductionmentioning
confidence: 99%